Advances and current challenges in calcium signaling. Issue 2 (14th January 2018) - Kudla, Jörg; Becker, Dirk; Grill, Erwin; Hedrich, Rainer; Hippler, Michael; Kummer, Ursula; Parniske, Martin; Romeis, Tina; Schumacher, Karin
Abstract : Content   Summary 414 I. Introduction 415 II. Ca 2+ importer and exporter in plants 415 III. The Ca 2+ decoding toolkit in plants 415 IV. Mechanisms of Ca 2+ signal decoding 417 V. Immediate Ca 2+ signaling in the regulation of ion transport 418 VI. Ca 2+ signal integration into long‐term ABA responses 419 VII Integration of Ca 2+ and hormone signaling through dynamic complex modulation of the CCaMK/CYCLOPS complex 420 VIII Ca 2+ signaling in mitochondria and chloroplasts 422 IX A view beyond recent advances in Ca 2+ imaging 423 X Modeling approaches in Ca 2+ signaling 424 XI Conclusions: Ca 2+ signaling a still young blooming field of plant research 424   Acknowledgements 425   ORCID 425   References 425 Summary: Temporally and spatially defined changes in Ca 2+ concentration in distinct compartments of cells represent a universal information code in plants. Recently, it has become evident that Ca 2+ signals not only govern intracellular regulation but also appear to contribute to long distance or even organismic signal propagation and physiological response regulation. Ca 2+ signals are shaped by an intimate interplay of channels and transporters, and during past years important contributing individual components have been identified and characterized. Ca 2+ signals are translated by an elaborate toolkit of Ca 2+ ‐binding proteins, many of which function as Ca 2+ sensors, into defined downstream responses. Intriguing progress has been achieved in identifying specific modules that interconnect Ca 2+ decoding proteins and protein kinases with downstream target effectors, and in characterizing molecular details of these processes. In this review, we reflect on recent major advances in our understanding of Ca 2+ signaling and cover emerging concepts and existing open questions that should be informative also for scientists that are currently entering this field of ever‐increasing breath and impact.